High Performance Work Practices Method Using Human Performance Technology: Systematic Literature Review - Dwita Setiyani; Ade Irma Anggraeni (Cita konsultindo, 2024)
Performance appraisal is an activity conducted by groups or individuals in a company with the aim of evaluating employee performance based on specific indicators. The purpose of this evaluation is to determine the level of employee performance, provide fair job opportunities, and enhance employee motivation and performance. The objective of this research is to review the literature that employs the Systematic Literature Review (SLR) method, while considering several aspects such as previous research on employee performance appraisal and human performance technology. Initially, the search was limited to 450 journals. Then, a review and further screening were conducted, resulting in 161 remaining journals using inclusion and exclusion criteria, yielding 17 journals that met the requirements. This research was conducted over several years to assess employee performance. Therefore, this systematic literature review is carried out to identify the methods used for employee performance appraisal and mentions that optimization algorithms and fuzzy comprehensive methods are used as evaluation methods to assess performance appraisal methods.